Konsep Pendidikan Berbasis Adab Menurut Buya Hamka - Khoir, Mulyanto Abdullah; Hartanto, Rudy; Priyanto, Catur; Mustamik, Khoirul (TSAQOFAH, 2025)
The concept of adab-based education according to Buya Hamka emphasizes the integration of knowledge, reason, and morals in forming individuals with noble character. Education is not only oriented towards the transfer of knowledge, but also towards the formation of character based on Islamic values. Hamka emphasized that reason as a gift from God must be utilized properly in seeking knowledge, while knowledge must be directed towards the right goals according to Islamic teachings. In addition, adab-based education includes respect for Allah, the Messenger of Allah, oneself, and fellow human beings as part of the formation of a complete personality. In social life, adab is the foundation for maintaining trust, building relationships, and obeying applicable rules. Therefore, this concept remains relevant in forming a generation that is not only intellectually superior, but also has strong morals and spirituality in facing the challenges of the times.